In Vivo Metabolism of Ibuprofen in Growing Conventional Pigs: A Pharmacokinetic Approach - Millecam, Joske; De Baere, Siegrid; Croubels, Siska; Devreese, Mathias (Frontiers in Pharmacology, 2019)
The juvenile conventional pig has been suggested as preclinical animal model to evaluate pharmacokinetic (PK), pharmacodynamic (PD) and safety parameters in children. However, still a lot of developmental changes in pig physiology need to be unraveled. While the in vitro ontogeny of pig biotransformation enzymes is getting more attention in literature, the in vivo developmental changes have not yet been investigated. Therefore, the aim of the current study was to evaluate the biotransformation of ibuprofen in conventional pigs ageing 1 week, 4 weeks, 8 weeks and 6-7 months after a single intravenous and oral administration of 5 mg/kg BW of ibuprofen, using a pharmacokinetic approach in a cross-over design for each age group. An UPLC-MS/MS method was developed and validated to determine 2-hydroxyibuprofen (2OH-IBU), carboxyibuprofen (COOH-IBU) and ibuprofen glucuronide (IBU-GlcA) in pig plasma. All three metabolites could be quantified in plasma and following pharmacokinetic parameters were determined: Cmax, Tmax , AUC0→6h, AUC ratio between parent drug and metabolite, and the absolute oral bioavailability of the parent drug ibuprofen. The plasma concentrations of the metabolites were always lower than those of ibuprofen. The bioavailability was high indicating limited pre-systemic biotransformation. The AUC ratio of 2OH-IBU and COOH-IBU/ibuprofen showed a significant increase at 4 weeks of age compared to the 1-week-old and 6-7-month-old pigs. Interestingly, the IBU-GlcA/ibuprofen AUC ratio did not change with age. The present study demonstrated that the main metabolites of ibuprofen in human are also present in growing pigs. The oxidative phase I metabolism of ibuprofen in growing conventional pigs did change with age. In contrast, age did not seem to affect the glucuronidation capacity of ibuprofen in conventional pigs, although more studies with other substrate drugs are needed to confirm this.